(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
The development of modern automation technologies and the dissemination of digital technical and technological solutions (tools) allows maximizing the positive effects generated by certain social processes and economic activities. Digital transformation has a significant impact on human capital indicators. The main formats for organizing the educational process using digital tools are considered, the development of tools for digital support of education in modern conditions is substantiated.